Has Strategic Purchasing Led to Improvements in Health Systems? A Narrative Review of Literature on Strategic Purchasing - Fred Matovu; Agnes Gatome-Munyua; Richard Sebaggala (Taylor & Francis Group, 2022)
ABSTRACTStrategic purchasing is noted in the literature as an approach that can improve the efficiency of health spending, increase equity in access to health care services, improve the quality of health care delivery, and advance progress toward universal health coverage. However, the evidence on how strategic purchasing can achieve these improvements is sparse. This narrative review sought to address this evidence gap and provide decision makers with lessons and policy recommendations. The authors conducted a systematic review based on two research questions: 1) What is the evidence on how purchasing functions affect purchasers' leverage to improve: resource allocation, incentives, and accountability; intermediate results (allocative and technical efficiency); and health system outcomes (improvements in equity, access, quality, and financial protection)? and 2) What conditions are needed for a country to make progress on strategic purchasing and achieve health system outcomes? We used database searches to identify published literature relevant to these research questions, and we coded the themes that emerged, in line with the purchasing functions-benefits specification, contracting arrangements, provider payment, and performance monitoring-and the outcomes of interest. The extent to which strategic purchasing affects the outcomes of interest in different settings is partly influenced by how the purchasing functions are designed and implemented, the enabling environment (both economic and political), and the level of development of the country's health system and infrastructure. For strategic purchasing to provide more value, sufficient public funding and pooling to reduce fragmentation of schemes is important.